THE BASIC PRINCIPLES OF LI-WI TECHNOLOGY AT THE IOT CONCEPT - Одарченко, Р. С.; Пробита, Д. М.; Третяк, І. В. (Science-based technologies, 2017)
This article deals with the problem of congestion in the frequency range in operation of wireless technologies in the concept of the Internet of things. Here is analyzed the main characteristics of PLC technology, Ethernet, Wi-Fi, ZigBee. There are some disadvantages of using the same frequency. This problem could be overcameby combining the best characteristics of each technology, as well as the addition of a completely new range of information transfer concept of visible light. The advantages of the new concept are reducing energy consumption, higher data rates without special permits and licenses, minimization of the harmful effects, simplicity of implementation. The elaborate list of pros and conspresented in the "Basic principles of Li-Wi technology at theIoT concept".Researches let us to evaluate the possibility of the development and using this technology in our future.